Bacterial Expression and HTS Assessment of Soluble Epoxide Hydrolase Phosphatase. (August 2016) - Klingler, Franca-Maria; Wolf, Markus; Wittmann, Sandra; Gribbon, Philip; Proschak, Ewgenij
Soluble epoxide hydrolase (sEH) is a bifunctional enzyme that possesses an epoxide hydrolase and lipid phosphatase activity (sEH-P) at two distinct catalytic domains. While the physiological role of the epoxide hydrolase domain is well understood, the consequences of the phosphatase activity remain unclear. Herein we describe the bacterial expression of the recombinant N-terminal domain of sEH-P and the development of a high-throughput screening protocol using a sensitive and commercially available substrate fluorescein diphosphate. The usability of the assay system was demonstrated and novel inhibitors of sEH-P were identified.